2015
DOI: 10.5812/ircmj.9244
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-17 Transcripts in PeripheralBlood Mononuclear Cells, a Link Between T-Helper 17 and Proinflammatory Responses in Bladder Cancer

Abstract: Background:Interleukin (IL)-17-producing CD4+ T helper (Th17) cells thatare known by producing IL-17 have recently been defined as a unique subset of proinflammatory helper cells. IL-17 is an inflammatory cytokine with robust effect on many cells and it can play important roles in pathogenesis of diverse groups of immune-mediated diseases.Objectives:The aim of this case-control study was to determine the gene expression of IL-6, IL-17, and transforming growth factor beta (TGF-β) in Iranian patients with bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Additionally, we found that cytotoxic cells, memory CD8 cells, mast cells, Th17 cells, Treg cells and other immune cell marker molecules were significantly upregulated. Baharlou R et al showed that Th17 cells might play an important roles in the antitumor immune response in early stage bladder cancer ( Baharlou et al, 2015 ). Next, we used CIBERSORT to further analyze the proportion of 22 immune cell subtypes in the ATM-MT group and found that the proportion of activated dendritic cells was significantly upregulated in the ATM-MT group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that cytotoxic cells, memory CD8 cells, mast cells, Th17 cells, Treg cells and other immune cell marker molecules were significantly upregulated. Baharlou R et al showed that Th17 cells might play an important roles in the antitumor immune response in early stage bladder cancer ( Baharlou et al, 2015 ). Next, we used CIBERSORT to further analyze the proportion of 22 immune cell subtypes in the ATM-MT group and found that the proportion of activated dendritic cells was significantly upregulated in the ATM-MT group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that macrophages secreting IL-17 family cytokines may play important roles in the pathogenesis of malignant tumors [ 14 ]. For example, it has been shown that IL-17A transcripts in peripheral blood mononuclear cells [ 15 ] and serum concentrations of IL-17A [ 16 ] were significantly higher in peripheral blood mononuclear cells in subjects with bladder cancer than those of controls. In animal experiments, it has been reported that IL-17A promoted bladder cancer growth [ 17 ], while IL-17-producing γδ T cells possibly play a key role in the Bacillus Calmette-Guéri (BCG)-induced recruitment of neutrophils to the bladder, which is essential for the antitumor activity against bladder cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IL‐17 upregulation was observed in BC with early stage tumors. They concluded that the IL‐17 probably decreased TGF‐β expressions in early stage of tumor progression (Baharlou et al, 2015).…”
Section: Immune Responsementioning
confidence: 99%